Measuring Dust System in the Air on Smartphone Devices - Phonrit, Orawan; Arnansanti, Natthakit; Laotrakulngam, Nattawat; Wattana, Nuanrath (JOURNAL OF INFORMATION SCIENCE AND TECHNOLOGY, 2020)
The objective of this research was develop dust in the air measuring system on smartphone devices. Because of ours concern about the problem of air pollution from smoke was coming from Indonesia that affect people health in Trang province in March, 2019. As a consequence, ours need to develop this system, by using concept of system development life cycle approach , database design and microcontroller device for system development. For research tool in this research was dust sensor device that setup system at SuanDusit University, Trang center and present dust value on Dust@SDU mobile application on smartphone device. The result found that the PM2.5 value from measuring dust system in 24 hours had close value with Pollution control department, since 20-22 in September, 2019 at Bankuan sub-district, Trang district in Trang province that the value from measuring dust system had higher value.